2017
DOI: 10.1016/j.jchf.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

INTERMACS Analysis of Stroke During Support With Continuous-Flow Left Ventricular Assist Devices

Abstract: Objectives We sought to evaluate predictors of stroke on LVAD from data available prior to implantation, and quantify stroke-related morbidity and mortality Background Stroke is a major complication after LVAD. Pre-implant factors that influence stroke are not well understood. Methods We evaluated all patients in the INTERMACS registry who were implanted with continuous-flow LVADs from May 1, 2012 to March 31, 2015. Preoperative risk factors for stroke, and stroke incidence, morbidity, and mortality were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
137
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(155 citation statements)
references
References 27 publications
2
137
0
6
Order By: Relevance
“…It is a leading cause of death that not only affects outcomes, but also the quality of life and transplantation candidacy. [8][9][10][11][12][13][14] The high incidence of stroke is mainly caused by an extremely delicate balance that exists between thrombosis and bleeding in patients receiving LVAD therapy. There is an intrinsic thrombogenicity associated with the device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a leading cause of death that not only affects outcomes, but also the quality of life and transplantation candidacy. [8][9][10][11][12][13][14] The high incidence of stroke is mainly caused by an extremely delicate balance that exists between thrombosis and bleeding in patients receiving LVAD therapy. There is an intrinsic thrombogenicity associated with the device.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidences of post-LVAD stroke across a variety of studies range from 10%-40%. [8][9][10][11][12][13][14] The cause of this common complication is multifactorial. LVAD therapy significantly alters a patient's coagulation profile.…”
mentioning
confidence: 99%
“…Hypertension, diabetes, and thrombocytopenia are all risk factors for thrombus formation in heart failure patients, which are not accounted for in the mock circulatory loop studies. Long‐term remodeling is another significant challenge for predicting outcomes from in vitro studies, including the formation of pannus at the inflow cannula and LV volume reduction due to reverse remodeling . Thus, any trends indicated by experimental measurements must be validated with clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the high incidence of stroke events, there is a high risk associated with stroke. In the third quarter of 2017, INTERMACS identified neurological dysfunction as the primary cause of death in 18.8% of reported deaths . Previous studies have identified the LVAD inflow cannula as a nidus for thrombus formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation